Does migration of skilled workers affect human capital investment in source countries? - Ngoma, Abubakar Lawan; Ismail, Normaz Wana (2015)
The debate over the effects of migration of skilled labour from developing to developed countries has parted into two major theoretical views. Traditionally migration of skilled labour was viewed to diminish the stock of human capital generated by source, developing countries. However, recent studies have held the view that prospect of migration for skilled workers, to where the return to skill is relatively higher than at home, induce would-be migrant workers to invest more in their education. In view of this, using panel dataset and random and fixed effect estimators, the effect of skilled labour migration on human capital investment was examined in a sample of 89 migrants-sending developing countries during the period 1975-2000. The result of the analysis revealed that the prospects of skilled labour migration exerts statistically significant effects on educational investments in migrants’ source developing countries. However, in the long run it leads to a reduction in the stock of better educated workers.